2021
DOI: 10.1007/s10902-021-00475-1
|View full text |Cite
|
Sign up to set email alerts
|

A Prototype Analysis of Self-Gratitude: Towards a Broadening of the Concept of Gratitude

Abstract: In the course of the last 20 years, gratitude has become a particularly active and fertile research field, notably in the USA and in the UK (e.g., Wood et al., 2010). Based on these studies, gratitude can now be considered a useful emotion in the promotion of mental health (for a review, see Jans-Beken et al., 2019). Interventions involving gratitude have demonstrably resulted in improvements in the areas of meaning of life and satisfaction with life (e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
(93 reference statements)
0
1
0
Order By: Relevance
“…Watkins et al (2003) proposed improving subjective wellbeing while studying the expression and experience of gratitude, where people with more gratitude would feel happier than less grateful people (Watkins et al, 2003). Lately, Tachon et al (2021) suggested that self-gratitude is associated with other important self-concepts such as selfacceptance and self-kindness, which are closely linked to individual wellbeing (Chamberlain and Haaga, 2001;Campos et al, 2016;Xu et al, 2016). Thus it can be construed that gratitude consistently establishes its relationship with greater happiness as it widens positive emotions and helps individuals experience pleasure from positive outcomes based on which we propose and test the following hypothesis:…”
Section: Gratitude and Workplace Happinessmentioning
confidence: 99%
“…Watkins et al (2003) proposed improving subjective wellbeing while studying the expression and experience of gratitude, where people with more gratitude would feel happier than less grateful people (Watkins et al, 2003). Lately, Tachon et al (2021) suggested that self-gratitude is associated with other important self-concepts such as selfacceptance and self-kindness, which are closely linked to individual wellbeing (Chamberlain and Haaga, 2001;Campos et al, 2016;Xu et al, 2016). Thus it can be construed that gratitude consistently establishes its relationship with greater happiness as it widens positive emotions and helps individuals experience pleasure from positive outcomes based on which we propose and test the following hypothesis:…”
Section: Gratitude and Workplace Happinessmentioning
confidence: 99%